Sistem Informasi Profil Desa Mulyosri Kecamatan Prembun Kabupaten Kebumen Berbasis Website Menggunakan Metode Waterfall - Aziz, Muhammad Abdul; anam, saiful (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2022)
The development of information technology and the internet is growing. This can be seen by the many places that provide internet facilities to obtain information. One of the uses of the internet in terms of information processing can be applied to the design of a website-based information system. Website-based information systems make it easy to disseminate information quickly and accurately. Based on the interviews conducted, the dissemination of information in Mulyosri Village still uses the manual method, thus making the agency's performance in providing information to the public less than optimal. To overcome this problem, a website-based information system was built to make it easier for the public to access information in Mulyosri Village. The development method used in this research is the waterfall method which consists of five steps of development, namely: (1) Requirement, (2) Design, (3) Implementation, (4) Verification, and (5) Maintenance. The system is made using the PHP programming language and uses a MySQL database. After the information system is complete, blackbox testing is carried out to see the feasibility of the system. This research produces a profile information system in Mulyosri Village that can be used and accessed by Mulyosri Village residents. In addition, based on the results of blackbox testing, it shows that the system has been running well and as expected. Thus it can be said that this system is feasible to use. Keywords: information system, village profile, website, waterfall method